Family Institution and Gender Equality: A Comparative Study in Islam and Feminism Perspective - Jamal Jamal; Muhammad Alif Rahmadi; Syamsul ‘Aimah; Muhammad Rayhan Al Biruni; Muhammad Dicky Mushoddiq (Tasfiyah: Jurnal Pemikiran Islam, 2022)
Feminism issues is a fascinating topic of discussion at this time. Problems such as rights and obligations in the family institution, male leadership and inequality against women were seen as clear patriarchal, oppressive, and dominant in regulating women and quite discriminative against them. Nevertheless, women's leadership was passively managed in family institutions. Hence, gender equality is only based on social phenomena and following environmental considerations rather than religious values. In contrast, Islam sees justice and leadership not only material and empirical but from metaphysical and spiritual aspects. Islam views that men and women need respect and love should be harmonious and balanced. This paper aims to examine how justice and equality are in the perspective of feminism and Islam. By using theological and philosophical approaches, as well as using critical analysis methods in this research. This research produces several conclusions. According to Islam, leadership in the family institution aims to elevate rights and dignity. Second, Islam emphasizes the principle of justice rather than the principle of equality in the family institution. Third, the concept of justice in the family institution by placing the roles of women and men in their respective capacities.